Standardization Guidelines for Chinese Medicine Rehabilitation - Research Base of Standards for Chinese Medicine Rehabilitation of National Administration of Traditional Chinese Medicine; Technology and Development Center for TCM of China; Runsheng XIE; Xiaoyan LAN; Weichi GUO; Yangyang WANG; Hui LI (康复学报)
To further facilitate the public health project"Standardization of Capacity Construction of TCM Rehabilitation Service", Chinese Medicine of Technology and Development Center for TCM of China and Research Base of Standards of Chinese Medicine Rehabilitation jointly promoted the special project of"Chinese Medicine Rehabilitation Standards"and carried out exemplary research according to the relevant requirements of the National Administration of Traditional Chinese Medicine. Guangdong Provincial Hospital of Chinese Medicine undertook the compilation of the Standardization Guidelines for the Rehabilitation of Chinese Medicine. Through literature research, investigation, expert demonstration, peer consultation, and with systematic analysis, the Standardization Guidelines were formed in three parts: general principles of stipulation, drafting requirements and standard system. The guidelines covered the contents of each stage for standard development, the basic drafting requirements of standard, and the overall structure and requirements of the standard system.